Numerical simulation of microscopic particle behavior and macroscopic relative viscosity of suspension with asymmetric flow field in a two-dimensional curvilinear channel - Taiki IIDA; Tomohiro FUKUI (Journal of Fluid Science and Technology, 2024)
Biomechanics is a field for mechanical study of the structure and function of living organisms, which finds many applications in various fields such as engineering, medicine and biology. Research in blood, systems showed that the blood volume is effectively changed by the strength and direction of shear stress on the vessel wall, also inducing changes in the vessel diameter. Most studies about wall shear stress in bends or branches are based on macroscopic single-phase flow, and more studies should be necessary to investigate wall shear stress distribution by multi-phase flow considering blood as a suspension. In this study, we focused on the flow characteristics of particle suspension, and aimed to analyze a flow field with asymmetrical differences in the shear stress on each wall of a two-dimensional (2D) parallel plates flow, i.e., a flow field with an asymmetric velocity profile. A 2D curvilinear channel was used to reproduce this flow field, and the regularized lattice Boltzmann method and the virtual flux method were used as the computational methods. Our results confirmed that the equilibrium positions were either two asymmetric points or a single point, depending on the radius of curvature of the channel and Reynolds number. The radial pressure gradient was found to be a major factor for the presence of a single equilibrium position. Furthermore, when the radius of curvature was decreased, the equilibrium position shifted closer to the inner wall side, and the relative viscosity of the suspension became higher because of the decreasing the distance between the particle and the inner wall.